The right of identity of the biological people born by assisted reproduction in doctrine, jurisprudence and peruvian legislation - Cárdenas Krenz, Ronald (2015)
The article discusses the issue of the right of people born through assisted reproduction, with the intervention of a third party, to know its biological origin from the perspective of the law, doctrine and jurisprudence in Peru.